Hubungan antara AI, Machine Learning, Dan Implikasinya Terhadap Responsivitas Bisnis - Nur Avia Aminia Junaedy; Nurul Asfiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
More time can be identified by applying AI to Big Data analysis in order to automate business processes on the platform. With the advent of AI and machine learning technologies, businesses can now interact with customers automatically because these technologies can provide honest feedback directly from customers. Many businesses currently use chatbots, which enable employees to communicate with customers around-the-clock. In business, machine learning can help determine the status of goods shipment. Data-data is time-based information that is analyzed to make it suitable for determining the status of the transaction. In addition, the use of machine learning can provide information about often purchased goods and assist consumers in examining goods that are highly valued